LENGTH SCALE INTERACTIONS IN THE FOLDING OF SANDWICH STRUCTURES - Hunt G.W.; Wadee M.A.; Ord A. (My University, 2001)
Compressed sandwich structures, comprising thin stiff faces separated by a thick layer of a soft-core material exhibit behaviour analogous to the geological phenomenon of parasitic folding in multi-layered media. Earlier cross-fertilization of ideas from structural mechanics into structural geology is extended, by considering the interactions of folding on two different length scales - overall buckling comprising a single half wave over the length of the structure, combined with short wavelength local wrinkling of a single face or layer. A new theory for such interactions is briefly presented and reviewed in the geological context. In the present problem, we see folding on different length scales at the same moment in time, implying a coupling of the instabilities associated with overall and local bucking.
Keywords: SANDWICH STRUCTURE; LOCALIZED BUCKLING; LENGTH SCALE INTERACTION